Proyecto de emprendimiento visual network: content creators - Miglio Piedra, Giacomo Lucca (2020)
Project concept: We are part of the communication services industry. Our target market is that of companies that require comprehensive communication services with an emphasis on digital marketing, branding and production of photography and video content. Our main product / service line is the management of digital communication for social networks, as well as audiovisual production. And it differs from competitors by possessing characteristics related to our marketing strategy due to product and price differentiation. Current situation: The organization was constituted as E.I.R.L, in June 2019. It is currently in the implementation phase / stage and first months of work. Your greatest challenge is attracting customers in the short term, and we will address this with our marketing strategy. Your greatest opportunity is our competitive advantage and the need of consumers for our products. Key factors: The key success factors of the project are the differential advantages that are graphed in the positioning related to the human factor; as well as the resources available for the optimal execution of the services (eg: digital cinema camera). In addition, there is the adequate economic capital for the correct implementation of the company. Further, we can compete on price in relation to some of our competitors, as will be seen in the later annexes. Financial requirement: To start, the project needs a capital of US $ 20,000.00. It will be used mainly for the implementation of the business with the minimum equipment necessary to provide the services of the company with the required personnel. The loan is already covered 100% since the investment was made by the founder of the company, coming from his own savings.